Interspecific and intraspecific variation of tree branch, leaf and stomatal traits in relation to topography in an aseasonal Amazon forest. (21st October 2022) - Zuleta, Daniel; Muller‐Landau, Helene C.; Duque, Alvaro; Caro, Natali; Cardenas, Dairon; Castaño, Nicolas; León‐Peláez, Juan Diego; Feeley, Kenneth J.
Abstract: Tropical forest responses to variation in water availability, which are critical for understanding and predicting the effects of climate change, depend on trait variation among trees. We quantified interspecific and intraspecific variation in 18 branch, leaf and stomatal traits for 19–72 dominant tree species along a local topographic gradient in an aseasonal Amazon terra firme forest, and tested trait relationships with tree size, elevation, and species' topographic associations. We further tested whether correlation and coordination of traits vary among trees, among species and/or among trees within species. Intraspecific trait variation was substantial and exceeded interspecific variation in 10 of 18 traits. For leaf acquisition traits, intraspecific variation was mainly related to tree topographic elevation, while most of the variation in branch, leaf and stomatal traits was related to tree size. Interspecific variation showed no clear relationships with species' habitat association. Although trait correlations and coordinations were generally maintained among trees and among species, bivariate relationships varied among trees within species, across habitat association classes and across tree size classes. Our results demonstrate the magnitude and importance of intraspecific trait variation in tropical trees, especially as related to tree size. Furthermore, these results suggest that previous findings relating interspecific variation with topographic association in seasonal forests do not necessarily generalize to aseasonal forests. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.